Determination of Implementation Cost Indicators for Water Supply Systems in the State of Pará, Brazil, as a Subsidy for the Elaboration of Economic-Financial Feasibility Studies - Barros, Arthur Julio Arrais; Teixeira, Luiza Carla Girard Mendes (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The research aimed to establish indicators for measuring the implementation costs of Water Supply Systems in the context of preparing economic-financial feasibility studies. To achieve this, the total implementation costs of 09 (nine) Water Supply Systems in Pará were surveyed and systematized, related to ongoing or recently completed projects in municipalities of the state; resulting in the identification of the system components, the establishment of cost indicators, and the validation of these indicators through the application of the methodologies of Jungles (1994) – adapted by Costa (2003) – and the National Secretary for Environmental Sanitation (2010). With the completion of this study, the current coverage and the projected increase in service provision were assessed through the implementation of interventions outlined in the scope of the construction, expansion, and improvement works of WSSs. Additionally, by establishing cost indicators for each unit within the Systems, it was possible to evaluate the convergence or divergence of the calculated indicators; notably, indicators for RWPS, RWP, SR, and ELR units exhibited a greater tendency toward centralization. In conclusion, based on the proposed validation, it was found that the methodology by Jungles (1994) did not accurately represent the estimated implementation costs for any of the units, whilst the methodology of the National Secretary for Environmental Sanitation (2010), due to minimal percentage differences, is more suitable for estimating overall budgets for basic sanitation system units.